1991
DOI: 10.1128/aac.35.6.1108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of tiacumicins B and C against Clostridium difficile

Abstract: Tiacumicins B and C are members of a novel group of 18-membered macrolide antibiotics with in vitro activity against Clostridium difficile. The MICs against 15 strains of C. difficile were 0.12 to 0.25 ,ug/mI for tiacumicin B, 0.25 to 1 ,ug/ml for tiacumicin C, and 0.5 to 1 ,ug/ml for vancomycin. The The tiacumicins are a group of 18-membered macrolide antibiotics originally isolated from the fermentation broth of Dactylosporangium aurantiacum subsp. hamdenensis (7,16). Tiacumicin B, the major antibiotic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
98
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 12 publications
3
98
2
Order By: Relevance
“…The MICs of OPT-80 for C. difficile reported by Theriault et al and Swanson et al were higher than those determined in this study (10,11). The treatment of CDAD with OPT-80 in a hamster model published by Swanson et al showed a higher efficacy than the treatment with vancomycin.…”
contrasting
confidence: 54%
See 3 more Smart Citations
“…The MICs of OPT-80 for C. difficile reported by Theriault et al and Swanson et al were higher than those determined in this study (10,11). The treatment of CDAD with OPT-80 in a hamster model published by Swanson et al showed a higher efficacy than the treatment with vancomycin.…”
contrasting
confidence: 54%
“…Also, OPT-80 has been shown to inhibit RNA synthesis by the Escherichia coli and Bacillus subtilis RNA polymerases (9). OPT-80 shows little or no systemic absorption (10). Earlier studies showed some activity against gram-positive aerobic and anaerobic organisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the hamster model, 4 which was later improved by Jeff Alder to develop an impressive data package, all vancomycin-treated animals died shortly after treatment ceased, whereas tiacumicin B-treated animals survived without apparent development of colitis. Recurrence of the infection is a major drawback of vancomycin treatment of colitis, and, on the basis of our results, Jake Clement delivered a presentation to Abbott management proposing Tiacumicin B as a product candidate.…”
mentioning
confidence: 99%